Let's follow the steps to solve the equation step by step, filling in any missing terms and selecting the appropriate descriptions.
Starting with the original equation:
1. \(17t + 8 - 18t = 11\)
First, we can combine like terms:
2. Combine like terms: \[ 17t - 18t + 8 = 11 \ -t + 8 = 11 \]
3. Now we will subtract 8 from both sides:
\(-t + 8 - 8 = 11 - 8\)
This simplifies to:
\(-t = 3\)
4. Next, we can multiply both sides by -1 to solve for \(t\):
\[
t = -3
\]
So, putting it all together, we have:
- Start with \(17t + 8 - 18t = 11\)
- Combine like terms: \( -t + 8 = 11\)
- Subtract 8 from both sides: \(-t = 3\)
- Multiply both sides by -1: \(t = -3\)
To fill in the blanks:
-
The missing terms include:
- "Combine like terms"
- "Add 8 to both sides"
- "Subtract 8 from both sides"
- "Multiply both sides by -1"
-
The final answer for \(t\) is: \[ t = -3 \]
So, the completed and simplified equation leads us to \(t = -3\).
Please let me know if you need anything else!